A Test for the Implementation–Maintenance Model of Reappraisal - Paret, Christian; Brenninkmeyer, Jessica; Meyer, Benjamin; Yuen, Kenneth S.; Gartmann, Nina; Mechias, Marie-Luise; Kalisch, Raffael (Frontiers in Psychology, 2011)
Reappraisal has been defined as a conscious, deliberate change in the way an emotional stimulus is interpreted, initiated in order to change its emotion-eliciting character (Gross, 2002). Reappraisal can be used to down-regulate negative emotions, including anxiety (reviewed in Kalisch, 2009). There is currently a strong interest in identifying the cognitive processes and neural substrates that mediate reappraisal. We have recently proposed a model (termed implementation-maintenance model or IMMO) that conceptualizes reappraisal as a temporally extended, dynamic and multi-componential process (Kalisch, 2009). A key tenet of IMMO is that reappraisal episodes are marked by an early phase of implementation that may comprise strategy selection and retrieval of reappraisal material into working memory, and a later phase of maintenance that may comprise working memory and performance monitoring processes. These should be supported by dissociable neural networks. We here show, using a detachment-from-threat paradigm and concurrent functional magnetic resonance imaging (fMRI), that reappraisal-related brain activity shifts from left posterior to right anterior parts of the lateral frontal cortex (LFC) during the course of a reappraisal episode. Our data provide first empirical evidence for the existence of two separable reappraisal stages. Implications for further model development are discussed.